CLIMATE CHANGES IMPACTS TOWARDS SEDIMENTATION RATE AT TERENGGANU RIVER, TERENGGANU, MALAYSIA - Mohd Khairul Amri, Kamarudin; Muhammad Barzani, Gasim; Hafizan, Juahir (2018)
The climate changes caused by rainfall and stream flow are not the major contribution the changing of water level. This study was carried out at Terengganu River Basin in wet and dry season to assess the sedimentation problem and its relationship with hydrological characteristic. Three parameters analyzed based on in-situ and ex-situ analysis according to the correlation matrix and linear regression methods. The TSS (mg/L), Turbidity (NTU) and SSC (mg/L) were higher during dry season compared wet season caused by El Nino phenomenon (January 2016). There are higher positive correlation between SSC and TSS, R²= 0.924 (wet season) and R² = 0.841 (dry season), the correlation between the observation (Q) and the TSS is no significant R² = 0.057 (wet season) and R² = 0.001 (dry season). The main contributors of sedimentation problems in Terengganu River caused by the climate changes phenomenon.